Locus of control and association with emotional stability among the medical students - Vidya, Bhagat; Nordin, Simbak; Khairi, Che Mat; Rohayah, Husain (2018)
Locus of Control refers to the extent to which people feel that they have control over the events that influence their lives. It has been realized that internal locus of control goes hand in hand with emotional stability. Current study aims at finding out the association between internal locus of control and emotional stability among the medical students. This was a cross-sectional study carried out on medical students of University Sultan Zainal Abidin; the participants were 100 included preclinical and clinical medical students of Year I to Year V of academic session 201712018 selected by using simple random sampling technique. Data were collected using levenson's Locus of Control scale and Eysanck personality inventory to study the association between Locus of Control and emotional stability. The data was statistically analyzed using SPSS Version 21. Out of 124 participants 100 students responded adequately among these respondents 34% (34) and 66% (66) were males and females, respectively. Pearson Correlation test showed significant association between internal locus of control and emotional stability is at the 0.01 level (2-tailed). The emotional stability was coeficient with locus of control. Internal locus of control found with -.910 in the lower bound and -.730 in the upper bound. Medical schools should make effort for realizing the significance of internal locus of control since it has its close association with emotional stability. These insights may be helpful in promoting healthiness in budding doctors. And also scope for related studies such as changing locus external to internal.